Sexual dimorphism in the cell number of the adult Drosophila brain - Narendra Pratap Singh; Susan T. Harbison (PLoS ONE, 2026)
Background Sexual dimorphism in animal behavior is common and may originate from differences in brain structure or function. In Drosophila , substantial male and female specific differences in gross brain anatomy, neuronal wiring, and behavior have been observed. However, it is not known whether global differences in the brain anatomy are strictly due to differences in neuronal patterning or if differences in cell number may also play a role. Principal findings During optimization of the assay for transposase-accessible chromatin with sequencing (ATAC-seq) to analyze gene regulation in adult brain cells we observed a need for more brain tissue in males compared to females. This suggested that male brains might have fewer cells. To test this hypothesis, we isolated total nuclei from adult brains and counted them using a flow cytometer. We found that female fly brains have approximately 30% more cells than male brains. These differences in cell number also correlated with differences in the physical size of the brain. Conclusions Our results suggest that male and female brains are not only differently wired but also have global differences in cell number that should be considered when analyzing differences in their behavior.